Contemporary management of localized penile cancer. Issue 1 (January 2011) - Shapiro, David; Shasha, Daniel; Tareen, Mohiba; Tareen, Basir
This article reviews the etiology, clinical presentation and diagnosis of localized penile cancer. We summarize the current literature concerning recent trends and advances in the treatment of localized penile cancer (<T2, node negative [N0]) through the use of a systematic review and meta-analysis. We discuss a generalized overview of the current treatment options. A total of 54 review articles, retrospective studies and case reports on conservative penile treatments were reviewed and screened for data on the efficacy of numerous therapies in carcinoma in situ, T1N0 and T2N0 patients. These data were analyzed, tabulated and discussed. Even though recurrence rates are higher in patients receiving penile-sparing options (compared with patients receiving radical penectomy), the locally recurrent cancers are highly treatable and these patients experience a higher quality of life.